Analisis Organisasi Kegiatan Ekstrakurikuler sebagai Wadah Pendukung Motivasi Berprestasi di Bidang Non-akademik pada Siswa - Devi Mayanti Magdalena Manullang; Desy Safitri; Sujarwo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Extracurricular activity organizations are student communities at school that run outside of class hours. This organization focuses on non-academic activities that usually capture student’s interests and talents. Through this platform, students need to develop their abilities and improve these abilities with valuable results. Through the organization of extracurricular activities, students can get a supportive environment to support student motivation to achieve. Achievements are not only in the academic field, but can be found in non-academic fields. Therefore, the results of this research show that internal roles and external roles are very important factors in building a supportive platform for achievement. Thus, it can be concluded that the organization of extracurricular activities can be a forum for supporting achievement motivation in the non-academic field for students if the internal and external organizations can build each other and establish good relationships, especially focusing on the target of developing student motivation to excel in the extracurricular field which is carried out.